Penerapan Selekta Kapita dalam Hukum Acara Perdata Terhadap Penyelesaian Sengketa di Indonesia - Fahrurrrizkianur , Akhmad (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
The application of selectivity in civil procedural law plays an important role in the process of resolving civil disputes in Indonesia. The selekta kapita principle allows judges to select and focus on the most relevant legal issues in a case, so that the litigation process can run more effectively and efficiently. This principle not only aims to speed up the judicial process, but also ensures that the interests of all parties involved in the dispute are fairly taken into account. Selekta kapita serves as a foundation for legal certainty and consistency in law enforcement in Indonesia. As such, its application in practice often faces challenges, such as limited access to legal resources, adaptation to social, economic and cultural dynamics, and difficulties in ensuring the enforceability of decisions in new cases. This article discusses the application of selekta kapita in civil procedure law and identifies the challenges faced in its implementation in Indonesia.